THE ARCHAEOLOGICAL HERITAGE AND ITS IMPORTANCE IN THE DEVELOPMENT OF PERU - Shady Solis, Ruth (2002)
Paper presented in the Intemational Seminar "Contribución del Control en la Gestión Ambiental y Patrimonio Cultural". It took place in the General Comptrollership oj the Republic,from ]une 3 to ]une 5, 2002. In this document, the problematic ofthe archeological goods in our country is treated, the historical importance they represent, to establish a cultural identity as a nation and also the wasted opportunity to become potential development axes; equally it's pointed the lack ofa coherentpolitic vision that prevents pillage and destruction of a historie legacy that can 't be renovated.